Optimization of Parking Public Transport Vehicles in Ostrava - Teichmann, Dušan; Dorda, Michal; Bínová, Helena; Ludvík, Martin (Promet - Traffic&Transportation, 2015)
A typical trait of public transport is a spatially scattered demand. A route net that is operated by a carrier (or several carriers) has to be adapted to the demand. Public transport vehicles that are not used during a period of a day are usually parked in defined parking lots that have a given capacity. When the vehicle goes from the place where its schedule ends (usually a terminus of the last connection served by the vehicle) to the place where the vehicle should be parked, a non-productive journey occurs. The same occurs at the beginning of the vehicle schedule as well. The main goal of the paper is to present a mathematical model that enables minimization of the total length of all the non-productive journeys. Functionality of the proposed mathematical model was tested in the conditions of a real bus public transport network.